2004
DOI: 10.1016/j.amjhyper.2004.02.016
|View full text |Cite
|
Sign up to set email alerts
|

Effects of the angiotensin II receptor blockers telmisartan versus valsartan on the circadian variation of blood pressure impact on the early morning period

Abstract: On a day of active therapy, telmisartan lowered both systolic and diastolic BP to a greater extent than valsartan for the last 6 h of the dosing interval. On a day in which a dose was missed, there was a notable trend for greater BP reduction during the latter part of the dosing interval on telmisartan versus valsartan. These results demonstrate that telmisartan achieved a greater effect than valsartan on BP during the early morning period in patients with hypertension.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
0
6

Year Published

2006
2006
2018
2018

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 118 publications
(72 citation statements)
references
References 14 publications
6
60
0
6
Order By: Relevance
“…The results of our analysis can be explained in part by the pharmacokinetic profile of telmisartan, which is characterized by a longer half-life than valsartan, 9,12 and by earlier pharmacodynamic studies using ambulatory BP monitoring that showed greater BP reductions on telmisartan compared with valsartan without the diuretic component. [16][17][18] This study also confirms and extends what had been shown regarding the combination therapies for the angiotensin II receptor blockers that use a higher dose of HCTZ (25 mg), 13,14 an option that has been shown to be increasingly useful in management of clinical hypertension. 3,12 Effects of angiotensin receptor blockers in combination with HCTZ A number of fixed-dose combination therapies of angiotensin receptor blocking agents and diuretics are currently available for the treatment of hypertension.…”
Section: Principal Findingssupporting
confidence: 81%
“…The results of our analysis can be explained in part by the pharmacokinetic profile of telmisartan, which is characterized by a longer half-life than valsartan, 9,12 and by earlier pharmacodynamic studies using ambulatory BP monitoring that showed greater BP reductions on telmisartan compared with valsartan without the diuretic component. [16][17][18] This study also confirms and extends what had been shown regarding the combination therapies for the angiotensin II receptor blockers that use a higher dose of HCTZ (25 mg), 13,14 an option that has been shown to be increasingly useful in management of clinical hypertension. 3,12 Effects of angiotensin receptor blockers in combination with HCTZ A number of fixed-dose combination therapies of angiotensin receptor blocking agents and diuretics are currently available for the treatment of hypertension.…”
Section: Principal Findingssupporting
confidence: 81%
“…The small loss in ambulatory BP-lowering effect of 1.0/0.7 mm Hg with aliskiren in the 24-48-h period relative to the 0-24-h period compares favourably not only with that observed with irbesartan (3.6/2.2 mm Hg) or ramipril (4.0/2.6 mm Hg) in this study, but also with that observed with other antihypertensive drugs in previous studies. [10][11][12][13] Although comparisons across different studies must be interpreted with caution, the only other study that has reported a p1 mm Hg loss of 24-h ambulatory SBP/DBP-lowering effect in the 24-48-h postdose period relative to the 0-24-h period involved amlodipine, 10 an agent well known for its long duration of action. This study also used a simulated non-adherence phase, involving morning and evening self-measurement of BP by patients at home, to Sustained BP reduction beyond 24 h with aliskiren P Palatini et al evaluate BP-lowering effects up to 72 h after dose (that is, following two successive simulated missed doses of treatment).…”
Section: Discussionmentioning
confidence: 99%
“…This study was undertaken to compare the antihypertensive effects and renal and vascular protective effects of the ARB telmisartan and the calcium antagonist amlodipine, which both exhibit a long-acting profile (3,6). In this study, the test drugs were administered as monotherapy to 2 groups of patients with untreated essential hypertension, unlike in many other large-scale studies that have been conducted in treated patients or patients on combination therapy.…”
Section: Discussionmentioning
confidence: 99%